Coexistence of Ankylosing Spondylitis and Multiple Sclerosis: A Case Report - Altınay Göksel Karatepe; Taciser Kaya; Muhteşem Gedizoğlu; Rezzan Günaydın; Salih Ürper (Archives of Rheumatology, 2006)
The neurological symptoms are rarely seen in patients with ankylosing spondylitis. Underlying reasons usually include progressive arachnoiditis, cauda equina syndrome, atlanto-axial subluxation and spinal fractures. In addition, the observation of multiple sclerosis-like symptoms and signs in some patients with ankylosing spondylitis has drawn attention to the coexistence of these two diseases. In this paper, an ankylosing spondylitis patient who developed the typical symptoms of multiple sclerosis during the follow-up was presented and the comorbidity was discussed in the view of current literature. (Rheumatism 2006; 21: 114-7)